Transforming Performance: The Role of Leadership Styles and Job Satisfaction in Pakistani Universities (Journal of Asian Development Studies, 2025)
The primary objective of this study is to examine the impact of leadership styles on employee performance, with job satisfaction serving as a mediating variable, in public and private universities across Pakistan. Primary data collected through questionnaire surveys from 300 participants were analysed by correlation, regression, and mediation techniques. The findings reveal that transformational, transactional, and laissez-faire leadership styles exert a significant positive influence on employee performance, whereas the autocratic leadership style negatively affects performance.  These results have important implications for university planners, suggesting that autocratic leadership should be avoided, as it undermines employee morale and adversely affects performance. This study examines the combined effect of four leadership styles on employees’ performance in higher education institutions, with job satisfaction as the mediating variable. It makes this research unique and distinguished from previous studies on leadership styles.